2010
DOI: 10.1007/s00213-010-2048-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin 1/orexin A in the ventral tegmental area enhances dopamine responses to cocaine and promotes cocaine self-administration

Abstract: Rationale Recent evidence indicates that the hypocretin/orexin system participates in the regulation of reinforcement and addiction processes. For example, manipulations that decrease hypocretin neurotransmission result in disruptions of neurochemical and behavioral responses to cocaine. Objectives To further assess the relationship between the hypocretin system and cocaine reinforcement, the current studies used microdialysis and in vivo voltammetry to examine the effects of hypocretin 1 on cocaine-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 45 publications
12
145
3
2
Order By: Relevance
“…Research teams have since demonstrated that blocking OX 1 R transmission by systemic or intra-VTA injection reduces motivated responding and reinstated reward-seeking behavior for palatable reinforcers including self-administered cocaine (Bentzley and Aston-Jones 2015; Borgland et al 2009; Boutrel et al 2005; James et al 2011; Muschamp et al 2014; Smith et al 2010). Reward suppression following hcrt/ox receptor antagonism may be driven in part by reductions in psychostimulant-evoked dopamine efflux within ventral striatum as has been supported using in vivo fast-scan cyclic voltammetry (España et al 2011; España et al 2010). …”
Section: Introductionmentioning
confidence: 92%
“…Research teams have since demonstrated that blocking OX 1 R transmission by systemic or intra-VTA injection reduces motivated responding and reinstated reward-seeking behavior for palatable reinforcers including self-administered cocaine (Bentzley and Aston-Jones 2015; Borgland et al 2009; Boutrel et al 2005; James et al 2011; Muschamp et al 2014; Smith et al 2010). Reward suppression following hcrt/ox receptor antagonism may be driven in part by reductions in psychostimulant-evoked dopamine efflux within ventral striatum as has been supported using in vivo fast-scan cyclic voltammetry (España et al 2011; España et al 2010). …”
Section: Introductionmentioning
confidence: 92%
“…Specifically, the breakpoint for cocaine is reduced by peripheral injection of SB-334867 but not the OX2R antagonist 4PT (Borgland et al, 2009; Brodnik et al, 2015; Prince, Rau, Yorgason, & Espana, 2015). This effect of the OX1R appears to specifically involve the ventral tegmental area where injection of SB-334867 recapitulates the lowering of the breakpoint (Espana et al, 2010) and OX-A injection increases breakpoint (Espana, Melchior, Roberts, & Jones, 2011). With these injections into the ventral tegmental area also found, respectively, to inhibit or enhance the effects of cocaine on dopamine signaling (Espana et al, 2011; Espana et al, 2010), it is likely that dopamine mediates these changes in the amount of effort expended to obtain this drug.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 97%
“…The dopamine neurons in the ventral tegmental area might be a crucial site of action for orexins to mediate these effects [85]. Accordingly, direct injections of orexin A in the ventral tegmental area increase dopamine levels in the nucleus accumbens [86,87]. Although most of the research on the involvement of orexins in drug addiction has focused on elucidating the function of OX1R [84,88], recent studies point to a role for OX2R in reward regulation.…”
Section: Reward Processingmentioning
confidence: 97%